Atividade física e sintomas neuropsiquiátricos em pacientes com demência de Alzheimer - Hernandez, Salma Stéphany Soleman [UNESP]; Vital, Thays Martins [UNESP]; Gobbi, Sebastião [UNESP]; Costa, José Luiz Riani [UNESP]; Stella, Florindo [UNESP] (FapUNIFESP (SciELO), 2011)
Is common the presence of neuropsychiatric symptoms in Alzheimerś disease (AD), this is resulted of anatomical and biochemical changes in the brain. The objective of present study was to look for papers relating physical activity and neuropsychiatric symptoms through a systematic review. The following data bases was accessed: Academic Search Premier, Biological Abstracts, Medline, PsycINFO, Pubmed, Scielo, Science direct on line, Sport Discus and Web of Science, using the following key-words: (Neuropsychiatric disturbances OR Neuropsychiatric symptoms OR Neuropsychological disturbances OR Aberrant behavior OR Aberrant behaviour OR Behavior disturbances OR Behaviour disturbances OR Behavior management OR Behaviour management OR Disruptive behavior OR Disruptive behaviour) AND (Alzheimer) AND (Exercise OR Motor intervention OR training OR Physical activity OR fitness), besides crossing the references in the selected articles. Eight studies had filled the inclusion criteria. It was possible to conclude there are evidences of positive results for agitation and sleep disturbances in patients with AD. However, there's no consensus of what kind of activity is better for these patients.
Physical activity and neuropsychiatric symptoms in elderly with Alzheimer's dementia
Keywords: Aged; Alzheimer disease; Behavioral symptoms; Exercise